Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
Volume 5: Ocean Engineering; CFD and VIV 2012
DOI: 10.1115/omae2012-83053
|View full text |Cite
|
Sign up to set email alerts
|

An Exploratory Study on the Working Principles of Energy Saving Devices (ESDs): PIV, CFD Investigations and ESD Design Guidelines

Abstract: A new Joint Industry Project (JIP) has been initiated recently by MARIN, called ESD-JILI ( ( ( (机理 机理 机理 机理) ) ) ), looking into the working principles and scale effects on Energy Saving Devices (ESDs). Three ESDs have been chosen for the investigations in the first phase. They were a preduct with a supporting stator in the duct, a pre-swirl stator with asymmetric blade design and Propeller Boss Cap Fins (PBCF). Measurements of forces and moments on all components of the ESDs have been carried out in selfpropu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 3 publications
2
19
0
Order By: Relevance
“…The contours represent the axial velocity magnitude, and the vectors represent the velocity magnitude and the direction of the plane. Figure 11 shows that the velocity distribution changes significantly at the plane center, and the result is similar to the result obtained by PIV (Dang et al, 2011). Due to the installation of the PBCF, the axial and rotational velocity magnitude at the plane center reduces, and there is even a small amount of reverse rotation.…”
Section: Comparison Of the Velocity Distribution After The Propellersupporting
confidence: 75%
See 1 more Smart Citation
“…The contours represent the axial velocity magnitude, and the vectors represent the velocity magnitude and the direction of the plane. Figure 11 shows that the velocity distribution changes significantly at the plane center, and the result is similar to the result obtained by PIV (Dang et al, 2011). Due to the installation of the PBCF, the axial and rotational velocity magnitude at the plane center reduces, and there is even a small amount of reverse rotation.…”
Section: Comparison Of the Velocity Distribution After The Propellersupporting
confidence: 75%
“…The measured increase of the propeller efficiency was from 1% to 1.5%. The Joint Industry Project (JIP; Dang et al, 2011) started by MARIN (Maritime Research Institute Netherlands) conducted a research on the flow field distribution and energy-saving mechanisms of PBCFs, and particle image velocimetry (PIV) was used in the experiment. The results showed that the velocity around the hub vortex decreases.…”
Section: Introductionmentioning
confidence: 99%
“…It is always difficult to judge sea trial results because the efficiency gains by the ESDs are often in the same order of magnitude as the uncertainties of the sea trial measurements. In addition to this, the scale effects of the ESDs can be rather large, because most of the ESDs are fitted to a place in the boundary layer of the vessel which differs from that in model scale [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Di Felice (2004) and Felli et al (2006) had gotten the main characteristics of propeller flow field measurement in a large cavitation tunnel by particle image velocimetry (PIV). Dang et al (2012) performed PIV measurements of the local flow fields of a ship's hull and around its energy-saving appendages. There have been some efforts in measuring full scale wake, for example, in project EFFORT and DALIDA.…”
Section: Introductionmentioning
confidence: 99%